Effects of Quaternary climatic fluctuations on the distribution of Neotropical savanna tree species. Issue 3 (26th February 2016) - Bueno, Marcelo Leandro; Pennington, R. Toby; Dexter, Kyle G.; Kamino, Luciana H. Yoshino; Pontara, Vanessa; Neves, Danilo Mesquita; Ratter, James Alexander; de Oliveira‐Filho, Ary Teixeira
Abstract : In order to develop niche models for tree species characteristic of the cerrado vegetation (woody savannas) of central South America, and to hindcast their distributions during the Last Glacial Maximum and Last Inter‐Glacial, we compiled a dataset of tree species checklists for typical cerrado vegetation (n = 282) and other geographically co‐occurring vegetation types, e.g. seasonally dry tropical forest (n = 355). We then performed an indicator species analysis to select ten species that best characterize typical cerrado vegetation and developed niche models for them using the Maxent algorithm. We used these models to assess the probability of occurrence of each species across South America at the following time slices: Current (0 ka pre‐industrial), Holocene (6 ka BP), Last Glacial Maximum (LGM – 21 ka BP), and Last Interglacial (LIG – 130 ka BP). The niche models were robust for all species and showed the highest probability of occurrence in the core area of the Cerrado Domain. The palaeomodels suggested changes in the distributions of cerrado tree species throughout the Quaternary, with expansion during the LIG into the adjacent Amazonian and Atlantic moist forests, as well as connections with other South American savannas. The LGM models suggested a retraction of cerrado vegetation to inter‐tableland depressions and slopes of the Central Brazilian Highlands. Contrary to previous hypotheses, such as the Pleistocene refuge theory, we found that the widest expansion of cerrado tree species seems to have occurred during the LIG, most probably due to its warmer climate. On the other hand, the postulated retractions during the LGM were likely related to both decreased precipitation and temperature. These results are congruent with palynological and phylogeographic studies in the Cerrado Domain.